Associating liver partition and portal vein ligation for staged hepatectomy in patients with colorectal liver metastases – Intermediate oncological results. Issue 4 (April 2016) - Björnsson, B.; Sparrelid, E.; Røsok, B.; Pomianowska, E.; Hasselgren, K.; Gasslander, T.; Bjørnbeth, B.A.; Isaksson, B.; Sandström, P.
Abstract: Background: Colorectal liver metastases (CRLM) not amenable for resection have grave prognosis. One limiting factor for surgery is a small future liver remnant (FLR). Early data suggests that associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) effectively increases the volume of the FLR allowing for resection in a larger fraction of patients than conventional two-stage hepatectomy (TSH) with portal vein occlusion (PVO). Oncological results of the treatment are lacking. The aim of this study was to assess the intermediate oncological outcomes after ALPPS in patients with CRLM. Material and methods: Retrospective analysis of all patients with CRLM operated with ALPPS at the participating centres between December 2012 and May 2014. Results: Twenty-three patients (16 male, 7 female), age 67 years (28–80) were operated for 6.5 (1–38) metastases of which the largest was 40 mm (14–130). Six (27.3%) patients had extra-hepatic metastases, 16 (72.7%) synchronous presentation. All patients received chemotherapy, 6 cycles (3–25) preoperatively and 16 (70%) postoperatively. Ten patients (43%) were rescue ALPPS after failed PVO. Severe complications occurred in 13.6% and one (4.5%) patient died within 90 days of surgery. After a median follow-up of 22.5 months from surgery and 33.5 months from diagnosis of liver metastases estimated 2 year overall survival was 59% (from surgery) and 73% (from diagnosis). Liver only recurrences (n = 8), were treated with reresection/ablation (n = 7) while lung recurrences were treated with chemotherapy. Conclusion: The overall survival, rate of severe complications and perioperative mortality associated with ALPPS for patients with CRLM is comparable to TSH.